LAMA PENYIMPANAN PADA SUHU DINGIN DAGING BROILER YANG DIBERI AIR PERASAN JERUK KASTURI (Citrus madurensis Lour.) - Wowor, Alwin K.Y; Ransaleleh, T. A.; Tamasoleng, M.; Komansilan, S. (Universitas Sam Ratulangi, 2014)
ABSTRACT STORAGE TIME OF BROILER MEAT THAT WERE GIVEN KASTURI LIME JUICE (Citrus madurensis Lour.)The purpose of this research was to determine the effect of storage time in a temperature range of -2°C to 4°C towards the pH value, moisture content, water holding capacity, and cooking loss of broiler meat that were given Kasturi lime (Citrus madurensis Lour.) juice. This research used the completely randomized design with 5 treatments which were (P1) = without storage; (P2) = 3 days of storage; (P3) = 6 days of storage, (P4) = 9 days of storage; (P5) = 12 days of storage and 4 repetitions. The variables observed were pH value, moisture content, water holding capacity, and cooking loss. The results showed that the storage time of broiler meat that were given Kasturi lime juice did not effect moisture content, water holding capacity, and cooking loss however it effect the pH value of the broiler meat. We concluded that storage of broiler meat in a temperature range of -2°C to 4°C retained the pH value, moisture content, water holding capacity, and cooking loss until 12 days. Keywords : Broiler meat, storage time, kasturi lime